Thermoelectric generators - Patel, Jay; Singh, Manmohan (Open Science Journal, 2021)
As the world is changing and developing with every passing day, the requirements of power are also increasing. There is a shift in utilizing the electrical energy as much as possible and for this reason, many countries have already made policies for completely ruling out the machines which don’t run on electricity. Apart from electricity, there are other forms of energy that can be used to convert that form into a more desirable form. For example, in a plant where the smoke comes out of the chimneys or in a car, the smoke carries a large amount of thermal energy with it. This energy is nothing but a waste and reduction in the efficiency of the systems. If somehow, this energy could be recovered, the efficiency can be increased. Thermoelectric generators serve for this purpose. Thermos electric generators get the heat and using the principle of heat conduction and p and n type materials, the heat can be directly converted into the electricity. There are many materials available in the market for p and n type but in our case, we chose silicon germanium which is also one of the most commonly used. First of all, a single module of thermoelectric generator will be made using p and n type material, as well as using conductive material and some ceramic substance. Then, the entire assembly will be made and this assembly will be exported to Ansys where custom materials will be added and applied on to the geometry. After performing analysis on full model, a comparative study will be presented in which the effect of material of conductive plate on to the voltage difference will be studied